Recent Advances in Imaging for Diagnosis, Monitoring, and Prognosis of Psoriatic Arthritis - Fassio, Angelo; Matzneller, Peter; Idolazzi, Luca (Frontiers in Medicine, 2020)
Psoriatic arthritis (PsA) is an inflammatory condition characterized by a strong heterogeneity and multifaceted behavior. The features of PsA are mainly divided in two subsets: axial and peripheral and both may be present at the same time. The peripheral subset can be characterized into further subgroups (articular, extra-articular). In recent years, the interest on extra-articular features (enthesitis and dactylitis) has steadily grown. In such a complex disease, imaging is often required in order to characterize type of involvement and to evaluate the radiological damage and progression of PsA. In addition, imaging plays a pivotal role in clinical practice, i.e. for axial involvement. Conventional radiology has been the main standard of reference for many years. However, in recent years, growing interest has developed over different imaging modalities: ultrasonography (US) and magnetic resonance (MRI). All these techniques play a role in diagnosis and in the follow up of our patients and cover all the subsets of the disease. US and MRI are more sensitive for detecting synovitis and this may be helpful for differential diagnosis, monitoring the treatment response and also to study the early or preclinical phase of the disease. In addition, other modalities are been investigated the field of PsA imaging. Computed tomography (CT), in particular dual energy-CT, and high-resolution peripheral CT (HRpQ-CT) might play in the future an important role in the assessment of bone damage, erosions and new bone formation. Regarding advanced functional imaging, FDG PET/CT is another interesting technique for exploring disease activity.